Upaya Kepolisian Dalam Menangani Tempat Kejadian Perkara Pembunuhan Di Jembatan Merah Putih - Mikhael Patsy Riupassa; Juanrico Alfaromona Sumarezs Titahelu; Denny Latumaerissa (Faculty of Law Universitas Pattimura, 2023)
According to Perkap 6 of 2019 in article 6 paragraph (1) regulates methods of carrying out investigations, one of which is TKP processing. Related to processing crime scenes to look for evidence, this can also be done in murder cases. Criminal acts of murder often occur in the midst of society. The initial police suspicion was that the victim died by committing suicide by dropping himself from the red and white bridge. However, when the police carried out further investigations, it was discovered that the cause of the victim's death was not suicide, but that the victim was deliberately thrown from the bridge by his two colleagues. This study aims to examine and analyze the efforts of the police in dealing with the crime scene on the red and white bridge and examine and analyze what factors are the obstacles for the police in handling the crime scene on the red and white bridge. This study uses Empirical Juridical Research. To analyze the problem, the Descriptive Analytical analysis technique is used with the technique of collecting and analyzing legal materials, namely Qualitative Analysis. The results of this study indicate that the process of handling a murder case at JMP, began with a public report regarding the discovery of a victim who was allegedly lifeless. again on the foundation of the pillars supporting JMP to Babinkantibmas,. Then the report was forwarded to the Ambon Bay Police. Regarding the processing of the TKP of the murder at JMP, the police referred to the Technical Instructions of the Indonesian National Police Number: 01/II/1982 concerning Handling of Crime Scenes (hereinafter referred to as JUKNIS 01/II/1982).